Keyframe-based modeling and tracking of multiple 3D objects - Kiyoung Kim; Lepetit, V; Woontack Woo (2010 9th IEEE International Symposium on Mixed and Augmented Reality, 2010)
We propose a real-time solution for modeling and tracking multiple 3D objects in unknown environments. Our contribution is two-fold: First, we show how to scale with the number of objects. This is done by combining recent techniques for image retrieval and online Structure from Motion, which can be run in parallel. As a result, tracking 40 objects in 3D can be done within 6 to 25 milliseconds per frame, even under difficult conditions for tracking. Second, we propose a method to let the user add new objects very quickly. The user simply has to select in an image a 2D region lying on the object. A 3D primitive is then fitted to the features within this region, and adjusted to create the object 3D model. In practice, this procedure takes less than a minute.